Sarcopenia: how to determine and manage - Jun Young Chung; Sang-Gyun Kim; Seong Hwan Kim; Cheol Hee Park (Knee Surgery & Related Research)
Abstract Background Understanding sarcopenia is becoming increasingly important as society ages. This comprehensive review covers the definition, epidemiology, causes, pathogenesis, diagnosis, prevention, management, and future directions for the management of sarcopenia, and the major issues related to sarcopenia in the knee joint. Main text Sarcopenia, a condition related to aging, is characterized by decreased muscle mass and strength, which significantly affects physical function. Its prevalence may vary by region and age, with reports of up to 50% prevalence in the elderly population. The potential causes of sarcopenia include neurodegeneration, poor nutrition, changes in hormonal effects, elevated levels of proinflammatory cytokines, and reduced activation of muscle satellite cells. Various pathogeneses, such as apoptosis, proteolysis, and inhibition of the signaling for increasing muscle mass, contribute to the development of sarcopenia. Generally, the diagnostic criteria for sarcopenia are based on reduced muscle mass, reduced muscle strength, and decreased physical performance, and can be assessed using various equipment and clinical tests. A healthy lifestyle consisting of a balanced diet, sufficient protein intake, and regular exercise is recommended to prevent sarcopenia. The management of sarcopenia involves resistance exercise, proper nutrition, and deprescribing from polypharmacy. In the future, pharmacological treatment and personalized nutrition may become alternative management options for sarcopenia. Finally, since sarcopenia can be associated with knee osteoarthritis and poor outcomes after total knee arthroplasty, appropriate management of sarcopenia is important for physicians treating knee-related conditions. Conclusions Sarcopenia is a significant pathological condition that needs to be recognized, especially in the older population. Although sarcopenia is common as aging occurs, it can be prevented by a healthy lifestyle. Currently, there are no approved drugs for sarcopenia; however, resistance exercise and proper nutritional supplementation are essential methods for managing sarcopenic conditions. Given its diverse causes, a personalized approach may be necessary to effectively manage sarcopenia. Finally, appropriate management of sarcopenia can contribute to the prevention and effective treatment of knee osteoarthritis.